In-groups, out-groups, and their contrasting perceptions of values among generational cohorts of Australians - Heritage, B.; Breen, Lauren; Roberts, Lynne (John Wiley & Sons, 2016)
Objective: Personal values guide, and are used to justify, behaviours both within and beyond organisational contexts. Baby Boomers, Generation X, and Generation Y are purported to vary in the values they espouse and hence their behaviours. The aim of this research was to examine and compare self-ratings and out-group perceptions of the importance of the four overarching clusters of values in Schwartz's circumplex model by generation. Method: A convenience sample of 157 participants (49 Baby Boomers, 47 Generation X, and 61 Generation Y) completed an online survey of self-rated values and perceptions of another generation's values. Results: Multivariate analyses identified that self-ratings of self-enhancement, openness to change, and conservation value clusters varied between generations (medium effect size), but self-transcendence did not. Out-group perceptions of generations varied across all four value clusters (very large effect size). We then compared each generation's self-ratings of value importance with perceptions of value importance provided by other generations (in-group/out-group comparisons). There were significant variations between self-ratings and perceived importance ratings provided by other generations for all three generations (large effect). Conclusions: Larger differences in other-ascribed than self-ascribed value importance across generations highlights the need to avoid actions based on generation value stereotypes, both within and beyond the workplace. Further research on a representative sample of the Australian population using a mixed-methods approach is recommended.